The First Case of Catheter-related Bloodstream Infection Caused by Nocardia farcinica - Heo, Sang Taek (The Korean Academy of Medical Sciences, 2010)
Nocardia farcinica is an emerging pathogen in immunocompromised hosts. Even though several species of Nocardia have been reported as causative pathogens of catheter-related blood stream infections (CRBSI), CRBSI caused by N. farcinica has not been reported. A 70-yr-old man with a tunneled central venous catheter (CVC) for home parenteral nutrition was admitted with fever for two days. Norcardia species was isolated from the blood through CVC and peripheral bloods and identified to N. farcinica by 16S rRNA and rpoB gene sequence analyses. This report emphasizes the rapid and correct identification of causative agents in infectious diseases in the selection of antimicrobial agents and the consideration of catheter removal.